Characterisation and utilization of three distinct male sterile systems in marigold (Tagetes erecta) - TEJASWINI, TEJASWINI; SANE, ANURADHA; GADRE, ARCHANA; GHATKE, MADHURI (The Indian Journal of Agricultural Sciences, 2016)
Three distinct male sterile systems were identified in marigold (Tagetus erecta L.) and classified as apetaloid, petaloid and gynomonoecious types based on their floral morphology. Detailed study indicated differences in their inheritance pattern, maintenance and utilization. Apetaloid male sterility was controlled by single recessive gene. Petaloid and gynomonoecious male sterile systems were under the control of cytoplasmic inheritance. Apetaloid sterile lines were maintained by intercrossing between sterile and fertile plants within the line. Petaloid and gynomonoecious lines were maintained by vegetative propagation. Besides utilizing male sterile system for hybrid seed production, the flowers of petaloid male sterile lines were found to be of commercial importance considering the flower head filled with all ray florets. SCAR marker was able to distinguish petaloid sterile types from apetaloid and gynomonoecious. For the first time, new male sterile systems are being reported in marigold with multiple sterile lines having significant commercial importance.